Sodium intake in US ethnic subgroups and potential impact of a new sodium reduction technology: NHANES Dietary Modeling - Fulgoni, Victor L (Nutr J, 2014)
BACKGROUND: Because excessive dietary sodium intake is a major contributor to hypertension, a reduction in dietary sodium has been recommended for the US population. Using the National Health and Nutrition Examination Survey (NHANES) 2007–2010 data, we estimated current sodium intake in US population ethnic subgroups and modeled the potential impact of a new sodium reduction technology on sodium intake. METHODS: NHANES 2007–2010 data were analyzed using The National Cancer Institute method to estimate usual intake in population subgroups. Potential impact of SODA-LO® Salt Microspheres sodium reduction technology on sodium intake was modeled using suggested sodium reductions of 20-30% in 953 foods and assuming various market penetrations. SAS 9.2, SUDAAN 11, and NHANES survey weights were used in all calculations with assessment across age, gender and ethnic groups. RESULTS: Current sodium intake across all population subgroups exceeds the Dietary Guidelines 2010 recommendations and has not changed during the last decade. However, sodium intake measured as a function of food intake has decreased significantly during the last decade for all ethnicities. “Grain Products” and “Meat, Poultry, Fish, & Mixtures” contribute about 2/3(rd) of total sodium intake. Sodium reduction, using SODA-LO® Salt Microspheres sodium reduction technology (with 100% market penetration) was estimated to be 185–323 mg/day or 6.3-8.4% of intake depending upon age, gender and ethnic group. CONCLUSIONS: Current sodium intake in US ethnic subgroups exceeds the recommendations and sodium reduction technologies could potentially help reduce dietary sodium intake among those groups.